Steinbeck Center tour
Doctor Susan Shillinglaw as Director of the Martha Heasley Cox Center for Steinbeck Studies, speaking to group of Salinans who came to MHCCfSS for private archival tour. The Steinbeck Center was in modular at this time. Original in safe.